Langerhans cell histiocytosis in adults [Langerhans hücreli histiyositoz] - (:unkn) unknown (My University, 2004)
Langerhans cell histiocytosis (LCH) is a rare disorder in which lesions contain cells with features similar to the Langerhans cells (LC) of the epidermidis. It was first described by Alfred Hand in 1893. The median age in adults at diagnosis is approximately 60 years and has a female preponderance (female/male: 1,1-2,1). Adult LCH most commonly affects skin, lung, and bone, although diabetes insipidus is a relatively common comorbidity. Involvement of liver, spleen, lymph nodes, and bone marrow is much less frequent. More than three quarters of patients presented with skin involvement, and a quarter has pulmonary lesions. Patients are either asymptomatic or manifest bone pain, skin lesion, dry unproductive cough with dyspnea, thirst, polyuria and central nervous system related symptoms. Clinical examination may reveal hepatosplenomegaly, lymphadenopathy, pneumothorax, exophthalmos, skin lesions resempling seborrheic dermatitis or nodular infiltration, neurologic dysfunction (cerebellar syndrome, space-occupying central nervous system lesions, hypothalamic-pituitary lesions). The basic lesion of LCH is formed by collection of pathologic LC (PLC). The demonstration of LC granules by electron microscopy or the expression of the CD1a antigen on the cell surface are necessary for a definitive diagnosis of LCH. S-100 positivity further supports the diagnosis. Diagnostic radiology has an important role in the management of LCH. On plain radiography, bone lesions are typically lytic. High resolution CT (HRCT) can show evidence of interstitial lung disease (reticular, reticulonodular, nodular opacities and diffuse cysts). NMR imaging has improved the diagnosis of CNS abnormalities in patients with LCH. Patients with limited involvement of LCH have excellent prognosis without need for systemic therapy. Symptomatic single lesions that potentially threaten organ function require radiation therapy. Patients with multifocal and systemic LCH can be treated with vinblastin, prednisone, vincristine, etoposide, 6-mercaptopurine and methotrexate. Patients who have otherwise refractory disease can benefit from 2 chlorodeoxyadenosine. The prognosis of the patients who didn't show any significant response to therapy during the first 6 weeks are poor with a mortality of less than 40 % at 5 years.